2016
DOI: 10.1093/schbul/sbw178
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Environmental Mechanisms Underlying the Expression of Psychosis: Introduction

Abstract: In this themed issue, a number of articles are presented that investigate environmental mechanisms in psychotic disorder. Below, we describe some of the challenges associated with this research, in terms of phenotypic definition, the nature of environmental impact and associated design and measurement issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…In addition, it has been shown that the exposure to environmental enrichment remarkably reduced the stress-sensitive phenotype induced by ancestral stress and also improved several levels of HPA axis function. From a clinical stance, the present findings support increasing evidence indicating that environmental factors in general [34], and daily-life experiences in particular [35], are potent factors in terms of influencing psychotic reactivity and expression. Research has been predominantly guided by diathesis-stress model, and there is a growing criticism regarding the disproportionate focus on stressors and negative life events and the negligence of positive environments.…”
supporting
confidence: 85%
“…In addition, it has been shown that the exposure to environmental enrichment remarkably reduced the stress-sensitive phenotype induced by ancestral stress and also improved several levels of HPA axis function. From a clinical stance, the present findings support increasing evidence indicating that environmental factors in general [34], and daily-life experiences in particular [35], are potent factors in terms of influencing psychotic reactivity and expression. Research has been predominantly guided by diathesis-stress model, and there is a growing criticism regarding the disproportionate focus on stressors and negative life events and the negligence of positive environments.…”
supporting
confidence: 85%
“…Individuals that carry a higher number of risk variants have a higher risk for developing psychotic disorder. Further, there is consistent evidence from numerous twin and family studies that the risk for developing a psychotic disorder is increased in first-degree relatives of patients with the disorder (Guloksuz et al, 2019;van Os, Reininghaus, & Meyer-Lindenberg, 2017a), which suggests a familial liability to psychosis (Islam et al, 2017). Familial liability may derive from a shared environment, i.e.…”
Section: Introductionmentioning
confidence: 92%
“…Another study of van Os and colleagues came to similar results: They found that subclinical psychotic experiences are transitory in about 80% of individuals, while around 20% go on to develop persistent psychotic experiences and 7% a psychotic disorder 8 . There is evidence that the clinical high-risk state is associated with an increased risk of psychotic disorders and its spectrum of related diagnostic categories such as schizophrenia, schizophreniform disorder, schizoaffective disorder, delusional disorder, brief psychotic disorder, depression/bipolar disorder with psychotic features, substance-induced psychotic disorder, psychotic disorder not otherwise classified 9 , 10 . A study of Rössler and colleagues differentiated between schizotypal signs (defined as the reduced capacity for close relationships as well as ideas of reference, odd beliefs, and suspicion/paranoid ideation) and schizophrenia nuclear symptoms (defined as thought insertion, thought-broadcasting, thought control, and hearing voices) and showed that the expression of these symptoms is predominantly influenced by stable traits around age 30, whereas the occasion-specific states are more influential at ages 20 and 50 11 .…”
Section: Introductionmentioning
confidence: 99%